Augmented Reality based on Image Processing (International Journal of Engineering and Computer Science, 2017)
Augmented Reality is hot trend in mobile industry, allowing addition of external data on top of camera input. Augmented Reality is used in areas such as gaming, navigation, tourism, and education in full interest. Using Digital image processing algorithms and computer vision different iPhone and android applications are created. Our concept is much like what we see and what our brain understand. We propose here to implement a real world object by capturing and follow several image processing technique to get an effective augmented image